Research on Opening Reignition Characteristics and Suppression Measures of 750 kV AC Filter Circuit Breakers - Jianguo Zhang; Pengcheng Sha; Feiyue Ma; Bo Niu; Xu Cai; Hui Ni; Junbo Deng (Energies)
The operation of converter valves in converter stations often results in high reactive power consumption and harmonic generation, necessitating measures to maintain reactive power balance and ensure power quality. To achieve this, the filter bank circuit breaker is frequently switched on and off during daily operation. In recent years, multiple incidents of circuit breaker breakdown during the opening process have been reported. In this study, power systems computer-aided design (PSCAD)/electromagnetic transients including DC (EMTDC) V5.0 electromagnetic transient simulation software is used to simulate and calculate the overvoltage and inrush current under different configurations of circuit breaker operating mechanism dispersion, opening phase angle, and operating speed. Additionally, the suppression effects of two measures are compared: “phase selection opening” and “phase selection opening combined with controlled opening speed” to mitigate overvoltage and inrush current. The results demonstrate that for BP11/13 filters, HP24/36 filters, and HP3 filters, the combined strategy of “phase-selective opening with controlled opening speed” is more effective in suppressing inrush current and overvoltage. However, for SC filters, the suppression effect of this combined strategy is not significant. Considering economic and practical factors, it is more reasonable to adopt the phase-selective opening measure for SC filters. These findings provide guidance for ensuring the safe operation of AC filter circuit breakers.